2017
DOI: 10.1200/jco.2016.69.5304
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy and Risk of Favorable and Aggressive Prostate Cancer

Abstract: PurposeThe association between exposure to testosterone replacement therapy (TRT) and prostate cancer risk is controversial. The objective was to examine this association through nationwide, population-based registry data.MethodsWe performed a nested case-control study in the National Prostate Cancer Register of Sweden, which includes all 38,570 prostate cancer cases diagnosed from 2009 to 2012, and 192,838 age-matched men free of prostate cancer. Multivariable conditional logistic regression was used to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…The doctrine that testosterone, the main substrate for DHT, promotes high‐grade cancer is being increasingly questioned. Loeb et al 15 concluded in a large nested case‐control study that testosterone replacement therapy did not increase the risk for aggressive prostate cancer. Higher levels of testosterone before androgen deprivation therapy have also been shown to decrease HR for prostate cancer deaths in a large meta‐analysis by Claps et al 16 …”
Section: Discussionmentioning
confidence: 99%
“…The doctrine that testosterone, the main substrate for DHT, promotes high‐grade cancer is being increasingly questioned. Loeb et al 15 concluded in a large nested case‐control study that testosterone replacement therapy did not increase the risk for aggressive prostate cancer. Higher levels of testosterone before androgen deprivation therapy have also been shown to decrease HR for prostate cancer deaths in a large meta‐analysis by Claps et al 16 …”
Section: Discussionmentioning
confidence: 99%
“…However, those electing testosterone replacement had a lower incidence of PC than those who did not as reported by a second study from Debruyne et al [37]. A further study on the use of testosterone replacement therapy in Sweden found an even more interesting observation of a significantly lower risk of aggressive PC (OR 0.44; 95% CI 0.32-0.61) [38]. Boyle et al [39] confirmed the safety of testosterone replacement in a meta-analysis of 11 trials in hypogonadal men where he found that the PC relative risk of 0.87 (0.30-2.50) was also lower, though non-significantly, after treatment…”
Section: Discussionmentioning
confidence: 72%
“…Prostate cancer risk categories were defined at diagnosis according to a modification of the National Comprehensive Cancer Network Guideline: Low‐risk: T1‐2, Gleason score of 2–6 and PSA < 10 ng/ml; intermediate‐risk: T1‐2, Gleason score 7 and/or PSA 10–20 ng/ml; high‐risk: T3 and/or Gleason score 8–10 and/or PSA 20–50 ng/ml; metastatic disease: T4 and/or N1 and/or PSA 50–100 ng/ml (regional metastases) or M1 and/or PSA > 100 ng/ml (distant metastases) . We clustered these risk categories into favorable‐risk prostate cancer (low‐ and intermediate‐risk), and aggressive prostate cancer (high‐risk and metastatic disease) . Date and cause of death were obtained from the Cause of Death Register, and deaths from cardiovascular diseases were defined as codes I00.0‐I99.9 (International Classification of Diseases, 10th revision).…”
Section: Methodsmentioning
confidence: 99%
“…32 We clustered these risk categories into favorable-risk prostate cancer (low-and intermediate-risk), and aggressive prostate cancer (high-risk and metastatic disease). 38 Date and cause of death were obtained from the Cause of Death Register, and deaths from cardiovascular diseases were defined as codes I00.0-I99.9 (International Classification of Diseases, 10th revision). We used four endpoints in the analyses: favorable-risk and aggressive prostate cancer, death of cardiovascular diseases and death of other causes.…”
Section: Endpoints Assessedmentioning
confidence: 99%